Research progress on substitution of in vivo method(s) by in vitro method(s) for human vaccine potency assays - Xuanxuan Zhang; Xing Wu; Qian He; Junzhi Wang; Qunying Mao; Zhenglun Liang; Miao Xu (Taylor & Francis Group, 2023)
Introduction Potency is a critical quality attribute for controlling quality consistency and relevant biological properties of vaccines. Owing to the high demand for animals, lengthy operations and high variability of in vivo methods, in vitro alternatives for human vaccine potency assays are extensively developed. Areas covered Herein, in vivo and in vitro methods for potency assays of previously licensed human vaccines were sorted, followed by a brief description of the background for substituting in vivo methods with in vitro alternatives. Based on the analysis of current research on the substitution of vaccine potency assays, barriers and suggestions for substituting were proposed. Expert opinion Owing to the variability of in vivo methods, the correlation between in vivo and in vitro methods may be low. One or more in vitro method(s) that determine the vaccine antigen content and functions, should be established. Since the substitution involves with the change of critical quality attributes and specifications, the specifications of in vitro methods should be appropriately set to maintain the efficacy of vaccines. For novel vaccines in research and development, in vitro methods for monitoring the consistency and relevant biological properties, should be established based on reflecting the immunogenicity of vaccines.